AKRONIM DALAM BAHASA INDONESIA TINJAUAN LINGUISTIK DAN SOSIO-POLITIS PERKEMBANGANNYA - Ana, Haerun (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 17 (2010): March 2010, 2010)
Acronym develops rapidly in the use of Indonesian language. The development, can be either linguistics or socio-politics. Linguistically, the development in the basics, however, it often does not obey the basics, therefore it influence it’s scientificity. Sociologically, acronym not only become the short form of phrase or name, but also become the slogan and houmor media. Politically, development of acronym is based on several reasons : (a) communicating identity (region), (b) spiritual natonal and religious motive, (c) myth in the past.